Innovative therapeutic modalities of purified platelet-derived growth factors on PDX1, Neurog3, and renin expressions in STZ-induced diabetic nephropathy and pancreatic injury - Elzallat, Mohamed; Hassan, Marwa; Fahmy, Hossam M.; El-Ahwany, Eman; Salama, Nagwan M.; Abu-Taleb, Hoda; Aboushousha, Tarek; Balata, Mahmoud; Mohammed, Dina Mostafa (Life Sciences, 2025)
Diabetic nephropathy is the predominant etiology of advanced renal disease, and its prevalence has increased significantly over recent years. The primary management strategy focuses on controlling identified risk factors; however, this approach only slows disease progression and cannot halt or reverse it. Therefore, novel therapeutic strategies are urgently needed. Forty-eight male rats were used in this study. After the experiment, kidney and pancreas tissues were removed and maintained for histopathological examination and gene expression analysis, and blood samples were taken to evaluate biochemical markers. Nutritional parameters were also evaluated. The diabetic nephropathy + PRP group and the diabetic nephropathy + L-GFs group showed reduced blood glucose levels and renin expression, alongside increased PDX1 and Neurog3 expression compared to the diabetic nephropathy group. Additionally, these groups exhibited decreased cytokine and malondialdehyde (MDA) levels, with significant improvements in superoxide dismutase (SOD) activity, hepatic function, and renal function biomarkers. Histopathological analysis of the kidneys and pancreas from both treatment groups showed significant improvements compared to the diabetic nephropathy group. In conclusion, administering platelet-rich plasma (PRP) and lyophilized growth factors (L-GFs) represents an innovative and promising treatment strategy for diabetic nephropathy and accompanying consequences.
CRIS-Team Scopus Importer:2025-08-29
Keywords: Diabetic nephropathy; Gene expression; Lyophilized GFs (L-GFs); Oxidative stress; Pancreatic injury; Platelet-rich plasma